Identity and Cultural Politics: NU’s Existence in the Dynamics of Power in East Java - Bintang, Adinda Gayatri; Alam Mahadika; Arfiati, Shera Nabila Nurizky; Pangestuti, Mutia; Rahma, Aisyah Aulia; Sari, Evi Puspita (Journal of Political Islam, 2025)
This study examines the existence of Nahdlatul Ulama (NU) in the dynamics of power in East Java using an identity and cultural politics approach while also examining the strategies used in establishing power relations at the local level. In the context of local politics, NU has strength from the cultural base of Islamic boarding schools, the network of ulama, and historical closeness to the grassroots community, making it an important actor in various regional political contestations. Using qualitative methods based on literature studies and documentation, this study analyzes how NU’s cultural strength is mobilized to form strategic alliances with other political actors through formal and informal channels. Thus, NU’s existence in East Java reflects cultural and spiritual strength and the ability to read and manage power dynamics at the local level.